(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Development of Corpus Linguistics today and its future we can find out the issues. A representation of language information for a specific reference study of the dynamics of change processes in the lexical structure of the language in various genres and allows analysis of lexical and grammatical features by different authors. It can be said that corpus linguistics has a wide range of users as its subject linguistic data intended for linguistic research in the interest of theoretical and practical basis of creating and using representative arrays has mechanisms.